2017
DOI: 10.1007/s10792-017-0799-5
|View full text |Cite
|
Sign up to set email alerts
|

Baseline demographics, clinical features, and treatment protocols of 240 patients with optic neuropathy: experiences from a neuro-ophthalmological clinic in the Aegean region of Turkey

Abstract: This study reported the demographics, clinical characteristics, and treatment protocols of optic neuropathies in a neuro-ophthalmology specialty clinic at a tertiary referral center in Turkey during the past decade. The data may be useful in assessing the global status of optic neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…4 , 32 – 34 A study in Turkey revealed that idiopathic-ON and MS were the most frequent etiologies, whereas NMOSD was the least frequent etiology. 35 These studies suggest that the frequency of ON etiologies varies among patients of different ethnic backgrounds. Early recognition of the specific cause of ON is important to prevent severe visual loss and avoid inappropriate treatments.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 32 – 34 A study in Turkey revealed that idiopathic-ON and MS were the most frequent etiologies, whereas NMOSD was the least frequent etiology. 35 These studies suggest that the frequency of ON etiologies varies among patients of different ethnic backgrounds. Early recognition of the specific cause of ON is important to prevent severe visual loss and avoid inappropriate treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies didn't prove any effective role but later on researchers found out that it is effective if given early 20 . Karti et al 9 , showed a promising role of steroids in cases of ischemic, MS related and NMOSD related ON however few authors didn't agree 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, literature search using pubmed and other search engines the subject topic is scarcely studied. Dhiman et al 8 , and Karti et al 9 , studied it in Indian and Turkish population respectively. However no such study is done so far in Pakistani population.…”
Section: Introductionmentioning
confidence: 99%
“…Non-arteritic anterior ischemic optic neuropathy (NAION) is the most common acquired primary optic neuropathy in individuals over the age of 50. 1 Factors which predispose certain eyes to develop NAION have been recognized. The primary risk factor for NAION appears to be a small-crowded optic disc.…”
Section: Introductionmentioning
confidence: 99%
“…Suggested additional identified factors associated with NAION include atherosclerotic vascular disease, diabetes mellitus, hypertension, hyperlipidemia, obesity and use of specific medications such as phosphodiesterase 5 inhibitors. [1][2][3][4] It has been suggested that NAION arise as a consequence of the obstruction of the axoplasmic flow due to the ischemia. NAION has been reported in cases, some relatively young, with optic nerve head drusen (ONHD).…”
Section: Introductionmentioning
confidence: 99%